Analysis of outcomes of a transoral circular stapled anastomosis following major upper gastrointestinal cancer resection. Issue 11 (8th February 2021) - Foley, Daniel M; Emanuwa, Emudiaga J E; Knight, William R C; Baker, Cara R; Kelly, Mark; McEwan, Ricardo; Zylstra, Janine; Davies, Andrew R; Gossage, James A
Summary: Background: Esophageal anastomoses performed following esophagectomy and total gastrectomy are technically challenging with a significant risk of anastomotic leak. A safe, reliable, and easy anastomotic technique is required to improve patient outcomes and reduce morbidity. Method: This paper analyses 328 consecutive patients who underwent transoral circular stapled esophageal anastomosis (ORVIL™) from a prospectively collected single-center database between December 2011 and February 2019. Results: Two hundred and twenty-seven esophagectomies and 101 gastrectomies were performed using OrVil™ anastomoses. The mean patient age was 63.7 years. Of 328 consecutive OrVil™-based anastomoses, there were 10 clinically significant anastomotic leaks requiring radiological or operative intervention (3.05%). Twenty-eight (8.54%) patients developed anastomotic stricture, all of which were successfully treated with endoscopic balloon dilatation (a median of 1 dilatation was required per patient). Conclusion: The OrVil™ anastomotic technique is reliable and safe to perform. This is the largest reported series of the OrVil™ anastomotic technique to date. Leak rates and anastomotic dilations were similar to other reported series. Based on our experience, we consider the use of the OrVil™ device for reconstruction after major upper GI resection to be safe and reliable.